2018
DOI: 10.1530/erc-18-0042
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor moonlighting in the prostate cancer microenvironment

Abstract: Androgen receptor (AR) signaling is vital for the normal development of the prostate and is critically involved in prostate cancer (PCa). AR is not only found in epithelial prostate cells but is also expressed in various cells in the PCa-associated stroma, which constitute the tumor microenvironment (TME). In the TME, AR is expressed in fibroblasts, macrophages, lymphocytes and neutrophils. AR expression in the TME was shown to be decreased in higher-grade and metastatic PCa, suggesting that stromal AR plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 166 publications
(163 reference statements)
0
25
0
Order By: Relevance
“…Increasing evidence supports the idea that CAFs are also sensitive to changes in tumor androgen levels, mediating the development of resistance to anti-androgen therapies. Indeed, AR signaling is active in CAFs, similarly to smooth muscle cells and fibroblasts in the normal prostate stroma and BPH, as well as in other stroma components (endothelial, immune cells) [140]. Chromatin immunoprecipitation sequencing (ChIP-seq) analysis in CAFs and PCa cells has demonstrated that upon testosterone exposure, AR in CAFs interacts with different genomic sites than in PCa cells, thus having distinct genomic targets in different cell types.…”
Section: Caf-mediated Resistance To Androgen Deprivation and Chemothementioning
confidence: 99%
“…Increasing evidence supports the idea that CAFs are also sensitive to changes in tumor androgen levels, mediating the development of resistance to anti-androgen therapies. Indeed, AR signaling is active in CAFs, similarly to smooth muscle cells and fibroblasts in the normal prostate stroma and BPH, as well as in other stroma components (endothelial, immune cells) [140]. Chromatin immunoprecipitation sequencing (ChIP-seq) analysis in CAFs and PCa cells has demonstrated that upon testosterone exposure, AR in CAFs interacts with different genomic sites than in PCa cells, thus having distinct genomic targets in different cell types.…”
Section: Caf-mediated Resistance To Androgen Deprivation and Chemothementioning
confidence: 99%
“…AR is encoded by a ubiquitously expressed gene located in the X chromosome at Xq11-12 and is particularly important in prostate development and homeostasis (Lubahn et al 1988). When dysregulated, however, AR activity is central to the onset, development and progression to metastasis of prostate cancer (PCa), the most common cancer diagnosed in males worldwide (Matias et al 2000, Gottlieb et al 2004, Knudsen & Penning 2010, Arora & Barbieri 2018, Centenera et al 2018, Cioni et al 2018, Li et al 2018, Nevedomskaya et al 2018, Paschalis et al 2018. In addition, AR mutations are linked to disorders of male sexual differentiation and development termed androgen insensitivity syndromes (AIS) (Hughes et al 2012, Mongan et al 2015, Gibson et al 2018 and to the rare adult-onset hereditary neurodegenerative disorder known as spinal and bulbar muscular atrophy (SBMA or Kennedy's disease; OMIM #313200) (Spada et al 1991, Badders et al 2018, Cortes & La Spada 2018, Lieberman 2018, Pennuto & Rinaldi 2018.…”
Section: Genetic Bases Of Drug Resistance In Prostate Cancermentioning
confidence: 99%
“…Physiological maintenance of the prostate strongly depends on androgen receptor (AR) signalling, which is also crucial for PCa development. While a large number of studies addressed the role of AR in PCa cells, only few reports focused on the molecular mechanisms of AR in stromal cells and its consequences for PCa progression and treatment in trans 11 , 12 . Expression of AR in macrophages was established in mice; however, the functionality of AR signalling in macrophages in relation to cancer development remained largely unknown 9 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%